Influence of Corporate Control and Ownership Structure on the Value of Firms Listed at the Nairobi Securities Exchange - Onguka, David; Kaijage, Eramus S.; Iraya, Cyrus M.; Kisaka, Sifunjo E. (European Scientific Journal, ESJ, 2018)
This study aimed at establishing the influence of corporate control and ownership structure on corporate values of companies listed at the Nairobi Securities Exchange. The paper tested the hypothesis that there is no significant moderating impact of ownership structure on the relationship between corporate control and corporate value growth based on Tobin Q and ROA measurements. The theory applied were agency theory, stewardship theory and stakeholder theory with the main anchoring theory being the agency theory. The study applied census survey for sixty four firms listed at the NSE. The time frame of analysis is five years between 2013 and 2017. Out of the 64 listed companies targeted, 58 were analyzed forming 90% of the population. The study applied census survey given that the population of the listed companies at the NSE were not many. Out of the 64 listed companies targeted, 59 were analyzed forming 92% of the population. Corporate control index was developed as a proxy for corporate control and ownership structure index was developed as a proxy for ownership structure. While ROA and Tobin Q were used to measure corporate value. The hypotheses were tested using both correlation and regression analysis. The key study variables of the listed companies were subjected to descriptive statistics and the results revealed a significant positive relationship between the variables. The study findings revealed significant moderating effect on the relationship between the value of the firm and its ownership structure.